2020
DOI: 10.1098/rspb.2020.0823
|View full text |Cite
|
Sign up to set email alerts
|

Higher temperatures lower rates of physiological and niche evolution

Abstract: Understanding rates and patterns of change in physiological and climatic-niche variables is of urgent importance as many species are increasingly threatened by rising global temperatures. Here, we broadly test several fundamental hypotheses about physiological and niche evolution for the first time (with appropriate phylogenetic methods), using published data from 2059 vertebrate species. Our main results show that: (i) physiological tolerances to heat evolve more slowly than those to cold, (ii) the hottest cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 68 publications
(117 reference statements)
3
46
0
Order By: Relevance
“…Our results corroborate and extend previous studies with more limited taxonomic coverage in land vertebrates, although the relationship of climatic breadths between axes was at times slightly positive (e.g., Bonetti & Wiens, 2014;Liu et al, 2020;Qu & Wiens, 2020). The general congruence between patterns in organisms of such a variety of evolutionary histories, ecologies and geographical distributions would imply that they are generated by common underlying evolutionary mechanisms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results corroborate and extend previous studies with more limited taxonomic coverage in land vertebrates, although the relationship of climatic breadths between axes was at times slightly positive (e.g., Bonetti & Wiens, 2014;Liu et al, 2020;Qu & Wiens, 2020). The general congruence between patterns in organisms of such a variety of evolutionary histories, ecologies and geographical distributions would imply that they are generated by common underlying evolutionary mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…This was first argued explicitly by Araújo et al (2013) in a comparison of temperature tolerances for ectotherms, endotherms, and plants, which found that tolerance to heat is largely conserved across lineages, whereas tolerance to cold varies between and within species. These patterns were later confirmed using explicit estimation of rates of physiological limits (Bennett et al, 2021;Qu & Wiens, 2020). Araújo et al (2013) argued that the most likely explanation for this discrepancy was that variation in lower thermal limits is a consequence of differences in thermodynamic effects of temperature on reaction rates, and most likely those responsible for maintaining ion homeostasis (Hosler et al, 2000;MacMillan et al, 2012), whereas, changes in heat tolerance would result from a limited variation in the ability of organisms to counter the destabilizing effects of high temperature on membranes and proteins (Angilletta, 2009).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…While these proximate mechanisms have been scrutinized in the macroecological literature, the ultimate (evolutionary) mechanisms driving range limit evolution in marine species are still poorly known (but see Sunday et al 2012). In terrestrial organisms, tolerance to heat is largely conserved across lineages, whereas tolerance to cold varies between and within species, a pattern that was interpreted as evidence for hard physiological boundaries constraining the evolution of tolerances to high temperatures (Araujo et al, 2013, see also Qu & Wiens, 2020). Indirect evidence of environmental tolerances can be obtained by recording the minimum and maximum latitudes of occurrence of a given species, given the widespread association between geographical distributions and physiological processes, particularly in marine fish (Stuart-Smith et al, 2015; Stuart-Smith, Edgar & Bates, 2017; Waldock et al, 2019; Dahlke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2017). Further, physiological tolerances to heat apparently evolve more slowly than those to cold (Qu and Wiens 2020). Alternatively, as the variation in temperature globally is larger at the lower physiological limits of species’ climatic niches, this may cause the negative relationship (Saupe et al.…”
mentioning
confidence: 99%